Investigation on the Prevalence of Coccidiosis of Chickens in Luang prabang - BOUNYAVONG , Somphanh; KEOHAVONG, Bounmy (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
The aim of this study was to investigate the prevalence of coccidiosisand identify the Eimeria spp caused of coccidiosis of chicken. All of the 100 chicks and fecal samples were collected from smallholder farms 50 samples and 50 samples from commercial farms in Luang Prabang district. The samples collections have been applied from October, 2015 to April, 2016. All of fecal and contents of each intestinal tract were examined microscopically in the laboratory using the simple floatation technique and Lesion scores of each Eimeria spp. were evaluated. The overall rate of coccidiosis was 55 (55%) were infected with coccidiosis and five Eimeria species namely:E. tenella, E.maxima, E. acervulina, E. brunetteand E. necatrix were identified; the prevalence was significantly (p<0.05).The chickens in smallholder farm were found 30 (60%) positive higher than the chickens in commercial farm 25 (50%); there was significantly (p<0.05). The mean lesion scores of Eimeria species infection were usually lower than +1(p>0.05).This study was identified the prevalence of coccidiosis for the first time in Luang Prabang district.In conclusion, coccidiosis was prevalence in Luang prabang district.Further additional researches and design control strategies needs to be implemented to reduce the loss due to coccidiosis.